The age at natural menopause of Chinese Han and Tibetan women - Chen, Shiqi; Yang, Liangbo; Chen, Furui; Qiu, Yu; Zhang, Jing; Li Ling, Jesse; Liu, Qiaolan; Gong, Yan (Frontiers in Endocrinology, 2025)
BackgroundStudies have reported that the age at natural menopause may vary between different ethnic groups. Chinese Han and Tibetan women exhibit substantial differences in their living environment, dietary habits, and lifestyle; however, few studies have specifically investigated the potential differences in their age at natural menopause. This study was designed to identify the discrepancy in the age at natural menopause between postmenopausal women of Chinese Han and Tibetan ethnicities.MethodsA cross-section study has been conducted on 5,562 Han and 1,049 Tibetan postmenopausal women who were recruited by the China Multi-ethnic Cohort study from May 2018 to September 2019. The participants have resided in Chengdu City and Aba Prefecture, respectively, with ethnicity set as the primary exposure variable. Linear and multinomial logistic regression model was used to assess the association of the age at natural menopause with influencing factors and odds ratios for the association between premature ovarian failure, early and late menopause with the ethnicity, and influencing factors.ResultsThe mean age at natural menopause of Han women was 0.74 year earlier than Tibetan women (P = 0.003). The Han women also showed a lower likelihood for experiencing late menopause with an adjusted odds ratio (95% confidence intervals) of 0.54 (0.34, 0.88) compared with the Tibetan women. Factors associated with later menopause have included older age at survey, ever married, high school and above educational level, annual household income of ≥200,000 RMB, no smoking, habit of eating spicy food, no history of severe food shortage, more gravidity, less parity, use of intrauterine device, and no history of using oral contraceptives.ConclusionsThe age at natural menopause of Chinese Han women was earlier than that of Chinese Tibetan women. Demographic, lifestyle, dietary habits, and reproductive factors may influence the age at natural menopause.